Global topics level 3 : English language discussion - Devine, Brian, (Educator) (Seoul Selection, 2020)
This book is written for students who have intermediate proficiency in English, but need to practice conversing on a variety of topics. Each section in the book is designed to intertwine discussion questions with interesting topical facts and opinions in order to guide students to speak as much as possible within the class period. Students will explore text and visual media to expand their knowledge of essential vocabulary for confident free talking.